Nilai-Nilai Pendidikan Islam Pada Kegiatan Ziarah Kubur dan Wisata Jama’ah Shomadiyah Mendolo Bumireso Wonosobo - Saefullah, Muhammad; Fuadi, Salis Irvan; Hidayat, Muhtar Sofwan (STAI Denpasar Bali, 2025)
This article discusses Islamic education in grave pilgrimage and tourism activities carried out by the Shomadiyah Mendolo congregation. The focus of the study in this study is what activities are carried out by the congregation in grave pilgrimage and tourism and what Islamic Education values ​​are contained in these activities. This study uses a qualitative field research method. The results of this study are as follows: the values ​​of Islamic Education contained in the grave pilgrimage and tourism activities of the Shomadiyah Mendolo congregation are faith values, muamalah values, moral values, spiritual values ​​and scientific values.